IMPLEMENTASI ACCESSIBLE TOURISM DI TMII JAKARTA - Lestari, Nurul Sukma; Wiastuti, Rachel Dyah; Triana, Ika (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Indonesia is a big country consisting of various tribes and has different cultures from one to another. From this came the idea to create a tourist site with a cultural background. Taman Mini Indonesia Indah is a tourist attraction established since 1975, an attraction with the theme of Indonesian culture. Taman Mini Indonesia Indah is still a tourist destination that has been chosen by many families. Likewise, schools that still do a lot of tourist visits for study tours Visitors to Taman Mini Indonesia Indah are still the second most in Jakarta. With the development of tourism, the concept of tourism for all it becomes an absolute necessity. Because throughout the world there is also a very significant increase in the number of tourists, and ten percent have special needs including elderly people, tourists with small children, pregnant women, tourists with permanent and temporary disabilities. Therefore, the purpose of this study is to find out to what extent Taman Mini Indonesia Indah has implemented accessibility in tourism in accordance with standards set by the UNWTO. The method used is descriptive qualitative, where data is obtained through field research, documentation, checklists and literature studies. The results of the study are found that vertical movements still need to be improved because visitors using a wheelchair cannot enjoy all the regional platforms. And the suggestion from the research is to continue to improve the facilities so that everyone can access them by adding braille letters to the brochure and adding audio announcements to every tourist attraction.